Development and characterization of sustainable active films incorporated with free and microencapsulated thyme essential oil for kiwi-fruit preservation - Marcovich, Norma E.; Ansorena, María Roberta (Frontiers in Sustainable Food Systems, 2025)
One of the main challenges facing the fresh-cut produce industry is maintaining the quality and food safety of these products to ensure both consumer satisfaction, which includes not further compromising the environment by following the global trend toward positive environmental footprints and the spirit of circular economy. Bio-based polymer blend films have emerged as a novel alternative to replace traditional plastics due to their biodegradability, sustainability, and environmental friendliness characteristics. In this work, we evaluated the properties of gelatin/chitosan composite films and coatings incorporated with thyme essential oil (TEO) in free form and microencapsulated in β-cyclodextrin. The incorporation of free and encapsulated TEO enhance the blocking properties of the films against UV–visible light (opacity values of 5.25 and 7.54 for 4% TEO content, respectively) and provides excellent in vitro antimicrobial and antioxidant properties. Films incorporated with encapsulated TEO showed improvement in tensile strength and water vapor permeability, with respect to both, neat composite films and films incorporated with free TEO, while films incorporated with free thyme essential oil exhibited enhanced elongation at break. Encapsulation can slow down the release rate of TEO from the films allowing the bioactive to remain active for much longer time. After 12 days of refrigerated storage (5°C), minimally processed kiwi-fruit coated with film forming solutions incorporated with encapsulated TEO showed reduced weight loss (4.2% reduction showed by kiwi slices coated with Ch-gel-TEO-βCD-4% formulation vs. 7.5% reduction exhibited by kiwi slices stored without coating), enhanced antioxidant properties (53% increment for kiwi slices coated with Ch-gel-TEO-βCD-4% compared to uncoated ones), as well as, significant reductions in the total mesophilic aerobic bacteria and yeast and mold counts (reductions of 3.37 and 2.93 Log CFU g−1, respectively, for kiwi slices coated with Ch-gel-TEO-βCD-4% formulation compared to kiwi slices stored without coating). The sensory acceptability kiwifruit coated with encapsulated TEO was the highest among tested samples, with no adverse effects on flavor and general acceptability. These results provide unique insights into new bio-packaging materials for the development of novel health foods materials with improved nutritional quality and sensory attributes, superior antimicrobial activity and extended shelf life.